Being Well-Connected Pays in a Disturbed World: Enhanced Herbivory in Better-Linked Habitats - Kristin I. Jinks (Diversity, 2020)
Seascapes are typically comprised of multiple components that are functionally linked by the movement of organisms and fluxes of matter. Changes to the number and spatial arrangement of these linkages affect biological connectivity that, in turn, can alter ecological functions. Herbivory is one such function, pivotal in controlling excessive algal growth when systems become disturbed. Here, we used microcosm experiments to test how the change to connectivity affects herbivory under different levels of disturbance. We applied network theory to measure types of connectivity at different scales (patch and whole system) and quantified herbivory by a crustacean mesograzer exposed to excess algae, mimicking pulse and press disturbances. We demonstrate that greater connectivity significantly enhances herbivory in Clibanarius virescens: Both the number of linkages and their spatial arrangement interact to shape the response of herbivory in systems to disturbance. Our findings highlight the value of controlled experiments for advancing theories about the potential effects of connectivity on important ecological functions, such as herbivory, and justify further investigation to measure how connectivity might affect the resilience of ecosystems. We posit that the variation in the type, and scale, of spatial linkages might have profound consequences for managing the capacity of ecosystems to respond to disturbance.